2007
DOI: 10.1158/1055-9965.epi-07-0124
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Solvents and Risk of Non-Hodgkin Lymphoma: Clues on Putative Mechanisms

Abstract: Malignant lymphomas are a group of diseases of uncertain etiology. Both environmental factors and genetic susceptibility have been reported as risk factors. We have conducted a population-based case-control study in Italy: all newly diagnosed cases of malignant lymphoma, in males and females ages 20 to 74 years in the 1991 to 1993 period, were identified; the control group was comprised of a random sample of the general population resident in each of the areas under study, stratified by sex and 5-year age grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…NHL has been associated with a number of occupations, including farmers, woodworking, rubber manufacture, mechanics, textile workers, janitors, printers, meat processors and hair dressers in epidemiological studies, although inconsistencies exist between studies 33 34. These studies suggest that pesticides, benzene, polychlorinated biphenyls and dyes might contribute to the aetiology of NHL 35 36. Our analysis revealed an increased risk for NHL among subjects in several employment groups.…”
Section: Discussionmentioning
confidence: 66%
“…NHL has been associated with a number of occupations, including farmers, woodworking, rubber manufacture, mechanics, textile workers, janitors, printers, meat processors and hair dressers in epidemiological studies, although inconsistencies exist between studies 33 34. These studies suggest that pesticides, benzene, polychlorinated biphenyls and dyes might contribute to the aetiology of NHL 35 36. Our analysis revealed an increased risk for NHL among subjects in several employment groups.…”
Section: Discussionmentioning
confidence: 66%
“…High-level occupational exposure to benzene among subjects with a familial history of haematological neoplasms was associated with an almost 30-fold excess risk of NHL, and subjects exposed to benzene with a history of immune system diseases ran a 16-fold excess risk 7. Although generated by small numbers, both findings seem to indicate immune system disruption as a mechanism of lymphomagenesis among benzene-exposed workers.…”
Section: Discussionmentioning
confidence: 88%
“…Solvents as a general category have been inconsistently associated with NHL [48]. Results from studies of TCE have been heterogeneous, and although some European studies reported positive associations, there was no consistent exposure-response pattern within or across the studies.…”
Section: Occupational and Environmental Factorsmentioning
confidence: 97%